Perancangan Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Website Menggunakan Metode Prototype - Rusmanhadi Nugroho; Eko Setia Budi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Tutoring is an activity carried out to help students solve problems in terms of learning. Tutoring is carried out in a conducive teaching and learning atmosphere to avoid learning difficulties. Tutors in tutoring help students overcome learning difficulties, develop an effective learning atmosphere, help students to be successful in learning so that they are able to adapt to educational demands. A web-based registration information system is a process for registering prospective students through a website page that uses internet media with the aim of registering themselves to become students at the school. Managing new student admission information online aims to create effective and efficient performance, because it is easier to get information and there is no need to waste a lot of time and money. Currently, not many tutoring schools in Indonesia use an online system for accepting new students. With the existing benefits and conveniences, this system should be developed by each school. Thus, the I Can Count tutoring registration system requires an online registration method via the official I Can Count tutoring website to make it easier for prospective students and admins to manage new student registration data. The method used in this research is data collection methods including interviews, observation and literature study. Meanwhile, the website method used is the Prototype method and the programming language used is HTML, CSS, PHP and Java Script and the database uses MySQL. The results of this research are that the website runs well and makes it easier for prospective students to obtain information and register at I Can Count tutoring, as well as making it easier for the I Can Count Admin to accept prospective students and store prospective student files.